PENGEMBANGAN MEDIA AUGMENTED REALITY POKOK BAHASAN SISTEM PENCERNAAN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SD - Nurahma, Sabela; Lukman Hakim; Lefudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to develop Augmented reality-based learning media on the subject of the human digestive system towards students' critical thinking skills in elementary school. The problem raised in this study is the low involvement of students in science learning due to the use of conventional media and the abstract nature of the subject matter. Using the research and development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The product developed is in the form of AR media that can be accessed via mobile devices and displays visualizations of the digestive system complete with interactive explanations and activity sheets. Validation was carried out by validator experts and tested through one-to-one, small group, and field trial stages. The validation results from three experts (subject matter, design, and language) showed that the media developed obtained a percentage of 83.33%, included in the "Very Valid" category. The practicality test was carried out through one-to-one with 3 students, obtaining a score of 89.33%, and a small group of 5 students obtained a score of 91.6% in the "Very Practical" category. To see the potential effects of the media, a field test was conducted on 17 students. The results showed as much as 94.1%, in the category of "Very Good". Based on the results of the study, it can be concluded that this Augmented reality media is suitable for use in learning.